Neolithic and Bronze Age ungulate footprint-tracks of the Severn Estuary: Species, age, identification and the interpretation of husbandry practices. (2nd January 2017) - Barr, Kirsten; Bell, Martin
Abstract : Ungulate footprint-tracks provide information regarding the species and age of animals. Combined with other datasets, this contributes to interpretation of seasonal husbandry patterns in the Severn Estuary, focusing on Bronze Age intertidal footprint-tracks at Redwick and Goldcliff East and the Late Neolithic site of Oldbury. Metric dimensions and morphology of modern contemporary ungulate footprint-tracks are used as analogues to help understand the species and age of prehistoric ungulates. Findings indicate that Dexter cattle and Soay sheep are metrically similar to British prehistoric ungulates. The prehistoric sites have a concentration of neonatal and juvenile individuals. Along with evidence provided by environmental data, faunal skeletal assemblages and lipid and isotopic analysis, this leads to the conclusion that the presence of younger animals and evidence at Brean Down for dairying is consistent with saltmarsh grazing activity in spring and summer.